(untitled) (Annals of Medical Research, 2021)
Aim: To compare the cyclic fatigue resistance at distilled water and %5.25 NaOCl of immersed ProTaper Gold (Dentsply Sirona, Ballaigues, Switzerland) and ProTaper Universal (Dentsply Sirona, Ballaigues, Switzerland) file systems.Material and Methods: The ProTaper Gold F2 (25.06v taper) and ProTaper Universal F2 (25.06v taper) file systems were immersed in distilled water andNaOCl for 5 minutes. After immersion process files were rotated at artificial canal with 60O curvature and a 5-mm radius until fracture occurred. Time to fracture and fractured lengths were recorded. Data were analyzed statistically using independent t-tests. Statistical significance was set at P .05. Results: ProTaper Gold files had a significantly higher resistance to cyclic fatigue than ProTaper Universal files (P .05). When ProTaper Universal immersed in distilled water showed higher resistance to cyclic fatigue than immersed in NaOCl solution (P .05).Conclusion: ProTaper Gold system more resistant than ProTaper Universal system to cyclic failure. The effect of NaOCl were higher on the ProTaper Universal system.Keywords: Corrosion, cyclic fatigue; NaOCl; ProTaper Gold; ProTaper Universal.